Gross Alpha and gross beta radioactivity and heavy metal concentration profiles of well water of the Calahunan Dump site, Mandurriao, Iloilo City - Amarante, Hena Charma; Basquez, Mark Anthony; Brunio, Christian Allan (2005.)
This study aimed to establish presence of radioactivity and concentration of heavy metals specifically lead and chromium in drinking water from wells within one-kilometer radius from the approximated center of of the Calahunan dump site.
Special Problem (Undergraduate, Bachelor of Science in Public Health)College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Well water -- Calahunan Dump sites -- Mandurriao, Iloilo; Mandurriao, Iloilo -- Calahunan Dump site